ANALISIS VISUAL VIDEO KAMPANYE UNICEF TENTANG DISABILITAS #SEPERTIKAMU 2021: Analysis of UNICEF's Disability Campaign Video #SepertiKamu 2021 - Tulus Hambawan; Elda Franzia Jasjfi (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2026)
Analysis of UNICEF's Disability Campaign Video #SepertiKamu 2021. This study discusses the visual analysis of UNICEF Indonesia’s campaign video titled “Apa Pendapatmu tentang Disabilitas” (What Do You Think About Disability), which was released in 2021 to commemorate the International Day of Persons with Disabilities. The campaign highlights the issue of social inclusion for persons with disabilities through personal narratives conveyed directly by individuals with disabilities. This study explores how visual elements such as camera shots, color, typography, and question-based segmentation are used to communicate messages of social inclusion. The research was conducted using a qualitative method with a descriptive approach, utilizing secondary data in the form of the campaign video and relevant academic literature. The findings indicate that visual techniques such as long shot (LS), medium long shot (MLS), and medium shot (MS), combined with eye-level camera angles, effectively strengthen the emotional connection between viewers and narrators. The use of blue as the primary color creates a reflective mood, while yellow as the secondary color adds a sense of optimism. Sans-serif typography enhances readability, especially for viewers with sensory disabilities. The video’s segmentation, built around stereotypical questions, presents a problem–solution narrative structure that effectively raises public awareness. This campaign functions not only as an informative medium but also as a platform for positive representation, portraying persons with disabilities as empowered and active individuals. The study emphasizes that inclusive visual storytelling can be a powerful social communication strategy for shaping public opinion and encouraging attitudinal change toward disability issues.